2015
DOI: 10.1186/s13023-015-0330-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral disturbance and treatment strategies in Smith-Magenis syndrome

Abstract: BackgroundSmith-Magenis syndrome is a complex neurodevelopmental disorder that includes intellectual deficiency, speech delay, behavioral disturbance and typical sleep disorders. Ninety percent of the cases are due to a 17p11.2 deletion encompassing the RAI1 gene; other cases are linked to mutations of the same gene. Behavioral disorders often include outbursts, attention deficit/hyperactivity disorders, self-injury with onychotillomania and polyembolokoilamania (insertion of objects into body orifices), etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 66 publications
0
44
2
1
Order By: Relevance
“…Interestingly, DRG2 is one of the genes on chromosome 17 at 17p11.2, which is related to Potocki-Lupski syndrome (PTLS) [45] and Smith-Magenis syndrome (SMS) [46] by point duplication and deletion, respectively. SMS patients exhibit craniofacial abnormalities, developmental delays, anxiety, hyperactivity, and circadian abnormalities [47,48]. Our preliminary analyses revealed that DRG2-deficient mice had hyperactivity and circadian abnormalities (H.R.L.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DRG2 is one of the genes on chromosome 17 at 17p11.2, which is related to Potocki-Lupski syndrome (PTLS) [45] and Smith-Magenis syndrome (SMS) [46] by point duplication and deletion, respectively. SMS patients exhibit craniofacial abnormalities, developmental delays, anxiety, hyperactivity, and circadian abnormalities [47,48]. Our preliminary analyses revealed that DRG2-deficient mice had hyperactivity and circadian abnormalities (H.R.L.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of SIB as a severe problem behavior is unique because SIB produces wounds to one's own person (Tate & Baroff, ). In addition, specific topographies and forms of SIB are one of the defining features of a number of behavioral phenotypes, such as Smith‐Magenis, Lesch–Nyhan, and Prader‐Willi syndromes (Didden, Korzilius, & Curfs, ; Elsea & Girirajan, ; Hustyi, Hammond, Rezvani, & Hall, , Lee, Berkowitz, & Choi, ; Nyhan, ; Poisson et al, ; Symons, Butler, Sanders, Feurer, & Thompson, ; Thompson & Caruso, ). For example, in a study by Symons et al (), 81% of their sample of individuals with Prader‐Willi syndrome engaged in a specific form of SIB (skin picking) and often in the same body locations.…”
Section: Differences Between Automatically and Socially Reinforced Sibmentioning
confidence: 99%
“…They have all been in contact with resource centres for rare disorders in Sweden and Norway and their challenging behaviour is followed by either their regional or local professionals. Knowledge regarding how to handle challenging behaviours in SMS are scarce (Poisson et al, 2015) and more research is needed, in addition a continuous effort to spread information to the local communities and professionals close to the families. In this study, we did not perform a thorough investigation of either intellectual level or communication, and that information is needed to further investigate whether there is a relation between behavioural problems and intellectual disability and communication.…”
Section: Discussionmentioning
confidence: 99%